Designing Social Service Markets Risk, Regulation and Rent-Seeking - Meagher, Gabrielle; Perche, Diana; Stebbing, Adam (ANU Press, 2022)
Governments of both right and left have been introducing market logics and instruments into Australian social services in recent decades. Their stated goals include reducing costs, increasing service diversity and, in some sectors, empowering consumers. This collection presents a set of original case studies of marketisation in social services as diverse as family day care, refugee settlement, employment services in remote communities, disability support, residential aged care, housing and retirement incomes. Contributors examine how governments have designed these markets, how they work, and their outcomes, with a focus on how risks and benefits are distributed between governments, providers and service users. Their analyses show that inefficiency, low‑quality services and inequitable access are typical problems. Avoiding simplistic explanations that attribute these problems to either a few 'bad apple' service providers or an amorphous neoliberalism that is the sum of all negative developments in recent years, the collection demonstrates the diversity of market models and examines how specific market designs make social service provision susceptible to particular problems. The evidence presented in this collection suggests that Australian governments' market-making policies have produced fragile and fragmented service systems, in which the risks of rent-seeking, resource leakage and regulatory capture are high. Yet the design of social service markets and their implementation are largely under political control. Consequently, if governments choose to work with market instruments, they need to do so differently, working with principles and practices that drive up both quality and equality.